Triazatruxene amine donor-based visible-light-responsive unsymmetrical squaraine dyes for dye-sensitized solar cells - Ingole, Kiran Balaso; Deshmukh, Shivdeep Suresh; Verma, Tushar Singh; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (ACS Applied Energy Materials, 2024)
Optimized charge-transfer dynamics at the dye-TiO2/electrolyte interface are required for an enhanced dye-sensitized solar cell (DSSC) device performance. Such an optimized interface enhances the charge-injection, dye-regeneration, and diminished charge-recombination processes, synergistically enhancing the device efficiency. In this study, octupolar-structured sensitizers are designed to improve the interaction between the dye and the redox electrolyte for increasing the dye-regeneration process upon photoexcitation. Accordingly, a set of unsymmetrical squaraine dyes with indoline and triazatruxene amine donor-based D-A-D dyes are designed (KV1-KV3), synthesized, and sensitized with a semiconducting metal oxide (TiO2) film. The sensitizer forms a monolayer on the TiO2 surface, leading to a dye-dye interaction, which broadens the absorption spectrum. The N atom of the triazatruxene amine donor was left unsubstituted in KV1, whereas a hexyl chain was installed in KV2 and KV3 and a branched alkyl chain was installed on the core N atoms in KV3 to control the self-assembly of dyes on the TiO2 surface. Self-assembly of alkyl groups wrapped in KV1-KV3 dyes on the TiO2 surface aids surface passivation and broadens the absorption profile, improving the light-harvesting capabilities. The DSSC devices based on KV2 exhibited a high power conversion efficiency of 7.85% (V-oc = 794 mV, J(sc) = 14.76 mA/cm(2), and FF = 67%), with an onset incident photon-to-current conversion efficiency response from 680 nm.
Keywords: aggregationof dyes; Dye-sensitized solar cells; metal-free organic dyes; self-assembly of dye; squaraine dyes; triazatruxene

Double anchoring squaraine dye with triazatruxene amine donor for dye-sensitized solar cells: sequential cosensitization for panchromatic light-harvesting - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
Dyes are firmly bound to a semiconducting TiO2 film using carboxylic acid anchoring groups for an efficient electron transfer from the excited state of dye to the conduction band (CB) of TiO2. Strong dye binding can be accomplished with multi-anchoring dye designs to improve photophysical characteristics, including high extinction coefficients, panchromatic absorption, post-sensitization modifications, and dark current suppression, besides enhancing the stability of the dye-TiO2 interface. Herein, a novel KV2D dye with double squaraine acceptor and double carboxylic acid anchoring groups is designed to achieve a high extinction coefficient (epsilon, 3.57 x 105M-1cm-1) and robust binding to the TiO2 film for an effective electron transfer. We systematically changed the amount of coadsorbent chenodeoxycholic acid (CDCA) to control the aggregation of dyes on the TiO2 surface that improves the power conversion efficiency (PCE, eta) for the devices based on the doubleanchoring KV2D. Out of these devices, KV2D: CDCA (1:10) based cell exhibited the best PCE of 5.26% with VOC of 754 mV, JSC of 10.41 mA/cm2, and ff of 67%. The sequential cosensitization studies were carried out with a far-red active dye to find the effect of the strong binding of the sensitizer to the TiO2 film. Interestingly, when di-anchoring, KV2D was sensitized first for 12 h and then sequentially cosensitized with far-red absorbing SQS4 for 5 h to achieve a PCE of 5.0% with VOC of 697 mV, JSC of 10.23 mA/cm2, and ff of 70% with panchromatic spectral response in IPCE upto 730 nm giving higher photocurrent generation.
Keywords: aggregation of dyes; Bulky donor unit; Double acceptor dye; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene

Auxiliary triazatruxene donor-based squaraine dyes for dye-sensitized solar cells: cis- and trans- configuration of dyes for modulating photophysical and electronic properties - Ingole, Kiran Balaso; Siby, Jesna; Pandya, Rinu; Vanka, Kumar; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemistry-an Asian Journal, 2026)
In DSSCs, dye regeneration efficiency and dye aggregation on the TiO2 surface can be modulated by using bulky aromatic donors wrapped with alkyl groups. Introduction of rigid aromatic rings around the donor unit of a dye will directly impact the driving force for electron injection and dye regeneration of a dye. In this work, we designed and synthesized KNS dyes with an auxiliary TAT donor integrated with a visible active squaraine dye. Here, octupolar-structured auxiliary TAT wrapped with alkyl groups is used as a strong donor and shelter to reduce the dye aggregation and charge recombination process. Further, to improve the light-harvesting efficiency and incident photon-to-current conversion efficiency of DSSC devices fabricated with KNS dyes, the central squaric acid unit has been modified by appending the electron-withdrawing dicyano group at the central squaric unit, and the trans-configured KNS1 dye was converted to cis-configured KNS2 dye. The power conversion efficiency of devices based on the KNS dyes was studied with and without 3 equivalents of CDCA by using the I-/I3 - electrolyte. Out of these devices, the KNS1: CDCA (1:3) based cell exhibited the best PCE of 6.25% with V OC of 793 mV, J SC of 11.08 mA cm-2, and ff of 71%.
Keywords: Bulky donor unit; Dye-sensitized solar cells; self-assembly of dye; squaraine dyes; triazatruxene